TOYOTA MOTOR CORPORATION'S BUSINESS ETHICS AND GLOBAL STRATEGY - Jhon Hendri; Selamet Riyadi (RADJA PUBLIKA, 2025)
The application of business ethics and moral integrity in Toyota's management system through the Kaizen philosophy as the basis for establishing a sustainable global strategy. The research approach uses a descriptive-analytical qualitative method with secondary data sources in the form of official Toyota Global reports, academic literature, and modern management theories. The analysis was conducted using the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that business ethics is placed as the main foundation of Toyota's management system, where the values ​​of Continuous Improvement and Respect for People serve as moral guidelines in decision-making, governance, and relationships between stakeholders. The integration of ethics with global strategy strengthens corporate legitimacy and public trust, while increasing corporate sustainability through a balance of economic, social, and environmental aspects. These findings confirm that the Kaizen philosophy is not only a management system, but a model of sustainable corporate ethics that can be adapted by other global companies as a guide to realizing corporate sustainability based on moral values ​​and social responsibility.